Identification and allocation of risks associated with ppp water projects in China - Xu, Yelin; Yang, Yunfang; P. C. Chan, Albert; F. Y. Yeung, John; Cheng, Hu (International Journal of Strategic Property Management, 2011)
As part of a comprehensive research into PPP implementation, nine case studies were scrutinized to explore the critical risks influencing the success of PPP water projects in China. Eleven critical risks were identified from real-life risk events through the content analysis. They were further analyzed in the aspects of risk origin and their allocation mechanism. It has been found that the government risks are considered as the most critical risks encountered by the Chinese project practitioners. To allocate risk, industrial practitioners should not only take into account of their management capability, but they should also pay more attention to the overall balance of risks and benefits, and risk guarantee through rigorous contract structure. The findings presented here are believed to enable interested investors to better understand the risks of PPP water projects in China.First Publish Online: 5 Oct 2011